From Belief to Practice: Teacher Self-Efficacy in Teaching Phonics to Preschool Students - Ryan Andisky Asrul; Sukardi Weda; Fitriyani Fitriyani (Hasanuddin University, 2025)
This study explores preschool teachers’ self-efficacy in teaching phonics to young learners in a bilingual early childhood setting in Makassar, Indonesia. Although phonics is a widely supported approach to early reading, its application across Indonesian preschools remains inconsistent, especially outside English-based programs. This research aims to examine how teachers perceive their self-efficacy in phonics instruction and understand how these beliefs influence classroom implementation. A descriptive qualitative method was employed, involving three preschool teachers. Data were collected through semi-structured interviews and classroom observations. The analysis was guided by Tschannen-Moran and Hoy’s (2001) framework covering instructional strategies, classroom management, and student engagement. Findings revealed that the participants demonstrated high or moderate-to-high self-efficacy in adapting phonics strategies, managing classroom behavior, and engaging students. Classroom observations largely confirmed alignment between teachers’ stated beliefs and their instructional practices. The study concludes that teacher self-efficacy significantly affects the quality and consistency of phonics instruction. It recommends that schools support teacher development through reflective practice, peer observation, and accessible teaching resources to improve early literacy outcomes.